Law Enforcement Against Online Gambling Promoters in Indonesia - Faisal Tanjung; Wahyudi Wahyudi; Listiyani Wulandari; Asri Rumalowak (Yayasan Cendekia Gagayunan Indonesia, 2025)
The development of technology is experiencing very rapid growth. One of them spreads to advertising activities where the advertising activities carried out become more effective and directed. However, these activities are also used by certain parties so that they become negative, such as online gambling advertising. Online gambling is also currently increasingly prevalent, one of which is caused by promoters who promote or advertise online gambling. The purpose of writing this scientific paper is to find out about law enforcement against online gambling promoters and the efforts of the Ministry of Communication and Information Technology (Kominfo) or which has now changed its nomenclature to the Ministry of Communication and Digital (Komdigi) in eradicating advertising content from online gambling. The methods used are historical approaches and legislative approaches. As a result of this writing, online gambling promoters are charged with article 27 paragraph 2 of Law Number 1 of 2024 and article 45 paragraph 3 of Law Number 1 of 2024 and the efforts of the Ministry of Communication and Information Technology (Kominfo) or which has now changed its nomenclature to the Ministry of Communication and Digital (Komdigi) in eradicating advertising content from online gambling have made their best efforts.